Regression analysis of end-point data from dynamic basic oxygen furnace model. - Guindon, René. (University of Ottawa (Canada), 1969)
The dynamic model described in this thesis for the Basic Oxygen Furnace (BOF) is an approximate one with the general characteristics of an oxygen steel furnace expressed through the thermodynamic relationships. It describes the behavior of a system with oxygen, iron, carbon, lime, silicon dioxide and maganese oxide in a simplified way. Also the effect of small amounts of silicon and maganese added to the bath are described. Simulation using this model reproduces most of the important aspects of date in the literature (except for the phenomenon of "slopping" and associated erratic behavior.) From the model, end-joint data was then generated for different initial conditions and a least squares equation was fitted to this data in terms of linear and non-linear variables. The characteristics of the endpoints that are of interest, that is, the time of blow, the final temperature and the amount of FeO formed, can then be predicted if the initial conditions are specified.
Keywords: Engineering, Electronics and Electrical.